Influence Of Working Group Activities Of Teachers On The Effectiveness Of Mathematics Teaching At EBC Besilau Laulara And EBC Fahisoi Lequidoe Academic Year 2021 - Antonio Guterres; Antonio Barreto; Domingas Ximenes Belo (Eduvest - Journal of Universal Studies, 2024)
The data analysis technique used in this research is descriptive statistics analysis techniques and inference analysis techniques with the aim of studying the research variable itself. In relation to the variables and samples mentioned, the techniques used to collect data are observation, questionnaire and documentation and according to Setiono and Riwonoto (2015) states that the Likert scale is the psychometric scale that is generally used in the questionnaire. And the instrument to be used to measure alternative responses is the Likert scale, this scale can be measured by choosing the perfect alternative answers, with the value used being 1 to 5 variables, so the researcher concluded that the questionnaire distributed to teachers with variables (X) is the influence of the activity of the teachers (GTP) and variable (Y) is the effectiveness of teaching mathematics, from the dependent and independent variables used by the researcher to find out whether or not the influence of one variable on another variable. Thus the results of the inference statistics analysis on the influence of the activity of the Working Group teachers (GTP) with a sample of 27 shows that the table = 0, 9 with a count = 2. Because the largest count of the table (2 > 0,9) is that we can say that we revenue Ho and accept Hi with his conclusion that there is a significant influence between the Activity of the Working Group dose teachers on the effectiveness of mathematics teaching (Y) at EBC Fahisoi Lequidoe and EBC Besilau Laulara.